Unraveling Passivation Mechanism of Imidazolium-Based Ionic Liquids on Inorganic Perovskite to Achieve Near-Record-Efficiency CsPbI2Br Solar Cells - Jie Xu (SpringerOpen, 2021)
Abstract The application of ionic liquids in perovskite has attracted wide-spread attention for its astounding performance improvement of perovskite solar cells (PSCs). However, the detailed mechanisms behind the improvement remain mysterious. Herein, a series of imidazolium-based ionic liquids (IILs) with different cations and anions is systematically investigated to elucidate the passivation mechanism of IILs on inorganic perovskites. It is found that IILs display the following advantages: (1) They form ionic bonds with Cs+ and Pb2+ cations on the surface and at the grain boundaries of perovskite films, which could effectively heal/reduce the Cs+/I− vacancies and Pb-related defects; (2) They serve as a bridge between the perovskite and the hole-transport-layer for effective charge extraction and transfer; and (3) They increase the hydrophobicity of the perovskite surface to further improve the stability of the CsPbI2Br PSCs. The combination of the above effects results in suppressed non-radiative recombination loss in CsPbI2Br PSCs and an impressive power conversion efficiency of 17.02%. Additionally, the CsPbI2Br PSCs with IILs surface modification exhibited improved ambient and light illumination stability. Our results provide guidance for an in-depth understanding of the passivation mechanism of IILs in inorganic perovskites.